A Hemophagocytic Lymphohistiocytosis Case with Newly Defined UNC13D (c.175G>C; p.Ala59Pro) Mutation and a Rare Complication - Yasemin Işık Balcı; Funda Özgürler Akpınar; Aziz Polat; Fethullah Kenar; Bianca Tesi; Tatiana Greenwood; Nagihan Yalçın; Ali Koçyiğit (Turkish Journal of Hematology, 2015)
Hemophagocytic lymphohistiocytosis (HLH) represents a severe hyperinflammatory condition with cardinal symptoms of prolonged fever, cytopenias, hepatosplenomegaly, and hemophagocytosis by activated, morphologically benign macrophages with impaired function of natural killer cells and cytotoxic T lymphocytes. A 2-month-old girl, who was admitted with fever, was diagnosed with HLH and her genetic examination revealed a newly defined mutation in the UNC13D (c.175G>C; p.Ala59Pro) gene. She was treated with dexamethasone, etoposide, and intrathecal methotrexate. During the second week of treatment, after three doses of etoposide, it was noticed that there was a necrotic plaque lesion on the soft palate. Pathologic examination of debrided material in PAS and Grocott staining revealed lots of septated hyphae, which was consistent with aspergillosis infection. Etoposide was stopped and amphotericin B treatment was given for six weeks. HLH 2004 protocol was completed to eight weeks with cyclosporine A orally. There was no patient with invasive aspergillosis infection as severe as causing palate and nasal septum perforation during HLH therapy. In immuncompromised patients, fungal infections may cause nasal septum perforation and treatment could be achieved by antifungal therapy and debridement of necrotic tissue.